A mezőgazdaság privatizációja a dél-dunántúli régióban - Kovács, Teréz (Tér és Társadalom, 1994)
Between 1990 and 1992, together with the decrease of the agricultural population, the number of agricultural workers dropped by a third in Southern Transdanubia. Currently in Tolna and Somogy, every fifth, in Zala every seventh, and in Baranya every eighth person lives on agriculture. The privatisation of agriculture is more advanced in Hungary than that of industry, but this process has not been completed yet, either. An important point of the process was the so-called co-operative personalisation that took place in 1992. Then all properties, except land were evaluated and the property was personalised based on different principles, such as years worked, amount of the income, and the value of the property taken into the co-operative in 1960. This meant that every person was told how much his or her share of the total property of the cooperative was worth. So they did not say that "this tractor is yours" but that "X amount of the total property of the co-operative is yours". If somebody still wanted to get his or her property in kind, he or she had to announce it in a certain time, he or she got his or her property but also lost his or her job, i. e. he or she had to resign from the co-operative. A very few used this opportunity. The property was divided among the present active members, the pensioners of the co-operative and those who had worked at least 5 years there, in the case of their deaths their descendants obtained the property, but only if they handed in their application by a certain címe. These were called outsiders, at national level 20% of the property belongs to them, 39% to the pensioners and 41% to the active members. The active members received the largest amount of property in Baranya. Following this, the obligatory transformation of the co-operatives took place. Most of the co-operatives (appr. 70) "transformed" into the same thing it had been before, i. e. a co-operative. Almost 10% of them are eliminated without a legal successor. The others were divided into smaller co-operatives, or go on functioning as Ltd.-s or Inc.-s. The privatisation of the land was an even more complicated process. In Hungary, unlike the other socialist countries, the land was not given back to the original owners. Still, if somebody had been deprived of land, he or she could get (following a long and slow process) a piece of land the value of which was the same as his or hers, but not the same that had been taken away. This procedure was called compensation. In Southern Transdanubia, the lands marked for compensation consisted 16.7% of the total area (datum of 28. Feb. 1994). This will grow by another 5 –10%. Approximately half of these lands are tilled by private persons, on the other half the co-operatives work, for extremely low wages. The compensated areas amount to one third of the total area in Tolna, the farmer economies are the most wide-spread in that county.